Efficiency of thiamethoxam for coffee leaf-miner control. II - Influence of timing of application via drip irrigation - Souza, Júlio César de; Reis, Paulo Rebelles; Rigitano, René Luis de Oliveira; Ciociola Júnior, Américo Iorio (Coffee Science - ISSN 1984-3909, 2007)
The coffee leaf-miner Leucoptera coffeella (Guérin-Mèneville, 1842) (Lepidoptera: Lyonetiidae) is the most important insect pest of coffee (Coffea arabica L.) in Brazil, where reductions in the production can reach 70 %. Application of the water dispersible (WB) granules formulation of the neonicotinoid insecticide thiamethoxam, via the irrigation water in drip irrigated coffee plantations is an alternative to the usual furrow application of granular formulations of insecticides for controlling this pest during the rainy season. In this work, the influence of application schedule of this insecticide, via irrigation water on the efficiency of coffee leaf miner control was investigated. The experiment consisted of four treatments: application of thiamethoxam 250 WG, via drip irrigation, in February (1), March (2) and April (3), and control (4). The percentage of mined leaves in selected branches was evaluated monthly and the concentration of insecticide in leaves determined from samples collected in August. Thiamethoxam was very efficient for the control of coffee leaf miner for all application times, with a protection period of about six months. There was an expressive loss of leaves in control due to pest attack which reduced production in approximately 58%.